Methodological considerations for the high sensitivity detection of multiple myeloma measurable residual disease. Issue 2 (23rd December 2019) - Soh, Kah Teong; Tario, Joseph D.; Hahn, Theresa E; Hillengass, Jens; McCarthy, Philip L.; Wallace, Paul K.
Abstract: Background: Recent advances in therapeutic interventions have dramatically improved complete response rates in patients with multiple myeloma (MM). The ability to identify residual myeloma cells (e.g., measurable residual disease [MRD]) can provide valuable information pertaining to patient's depth of response to therapy and risk of relapse. Multiparametric flow cytometry is an excellent technique to monitor MRD and has been demonstrated to correlate with patient outcome post‐treatment. To achieve the high sensitivity (one abnormal cell in 10 5 –10 6 cells) required for MRD evaluation, millions of cells have to be acquired and conventional immunophenotyping protocols are unable to attain these numbers, indicating the needs for alternative flow cytometric staining procedures. A bulk, "Pre‐lysis" method is the consensus approach for staining large number of cells, requires two red blood cell lysis steps, and can adversely affect epitope density. In this study, we tested the "Pooled‐tube" and "Dextran Sedimentation" staining procedures and correlated them with the "Pre‐lysis" method as potential alternative approaches. Methods: A total of 22 bone marrow aspirates from patients with plasma cell (PC) dyscrasia were processed in parallel using the "Pre‐lysis, " "Pooled‐tube, " and "Dextran Sedimentation" techniques. Stain indices were calculated and compared to assess their impacts on staining performance for each antibody used in the consensus panel. The recovery of normal and abnormal PCs, mast cells, and B cell precursors was enumerated and compared after their counts were normalized using fluorescent beads. The limit of blank, limit of detection, and lower limit of quantification were established using serial dilution experiments. Results: The staining performances of CD19 PECy7, CD27 BV510, CD81 APCH7, and CD138 BV421 were improved using the "Pooled‐tube" method when compared to "Pre‐lysis." "Pre‐lysis" was better at resolving CD56 using clone C5.9 but our results demonstrated similar improvement can also be achieved by "Pooled‐tube" when alternative CD56 PE clones were used. "Dextran sedimentation" yielded similar staining results when compared to "Pre‐lysis" for all the markers analyzed. The "Pooled‐tube" method, when normalized to "Pre‐lysis, " recovered higher numbers of total PCs (1.2 ± 0.2 times higher; p = .049), normal PCs (1.4 ± 0.26; p = .007), mast cells (1.46 ± 0.27; p = .003), and B cell precursors (1.42 ± 0.3; p = .011), but not abnormal PCs (1.09 ± 0.2; p = .352). There was no evidence that the recovery of cells was different between "Pre‐lysis" versus "Dextran Sedimentation." All three flow cytometric assays achieved a minimum sensitivity of 10 −5 and approached that of 10 −6 for detecting rare events. Conclusion: Both "Pooled‐tube" and "Dextran Sedimentation" staining procedures were comparable to the "Pre‐lysis" method and are suitable high sensitivity flow cytometric approaches that can be used to process bone marrow samples for MM MRD testing.